2019
DOI: 10.1021/acs.joc.9b01091
|View full text |Cite
|
Sign up to set email alerts
|

2-Substituted 1,4-Naphthoquinones in [6 + 4]-Cycloaddition with 8,8-Dicyanoheptafulvene

Abstract: This study demonstrates that classical lowest unoccupied molecular orbital reactivity of 2-substituted 1,4-naphthoquinones is possible to be reversed by deprotonation and application of the resulting dienolate as a 4π component in the higher-order [6 + 4]-cycloaddition proceeding in a completely pericyclic manner. 8,8-Dicyanoheptafulvene was shown to be an efficient 6π component in the developed reaction opening the access to functionalized cycloadducts in a diastereoselective manner by employing organocatalyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 68 publications
0
6
0
Order By: Relevance
“…An interesting utilization of 8,8‐dicyanoheptafulvene 68 a as a triene in a [6+4]‐cycloaddition was shown in 2019 (Scheme ) . As postulated by the authors, deprotonation of 2‐substituted‐1,4‐naphthoquinones 88 by appropriate Brønsted‐base organocatalyst (DABCO) led to the formation of dienolate 90 , which was used as a trienophile in the higher‐order cycloaddition with 8,8‐dicyanoheptafulvene 68 a , thus forming final, interesting policyclic derivatives 89 .…”
Section: Troponoid Systems In Organocatalytic Higher‐order Cycloadditmentioning
confidence: 99%
See 1 more Smart Citation
“…An interesting utilization of 8,8‐dicyanoheptafulvene 68 a as a triene in a [6+4]‐cycloaddition was shown in 2019 (Scheme ) . As postulated by the authors, deprotonation of 2‐substituted‐1,4‐naphthoquinones 88 by appropriate Brønsted‐base organocatalyst (DABCO) led to the formation of dienolate 90 , which was used as a trienophile in the higher‐order cycloaddition with 8,8‐dicyanoheptafulvene 68 a , thus forming final, interesting policyclic derivatives 89 .…”
Section: Troponoid Systems In Organocatalytic Higher‐order Cycloadditmentioning
confidence: 99%
“…An interesting utilization of 8,8-dicyanoheptafulvene 68 a as at riene in a[ 6 + +4]-cycloaddition was shown in 2019 (Scheme25). [34] As postulated by the authors,d eprotonation of 2-substituted-1,4-naphthoquinones 88 by appropriate Brønsted-base organocatalyst (DABCO) led to the formation of dienolate 90,which was used as atrienophile in the higher-order cycloaddition with 8,8-dicyanoheptafulvene 68 a,t hus forming final, interesting policyclic derivatives 89.D isappointingly,a ttempts to perform this reactioni na ne nantioselective manner were ineffective. Excellent diastereomeric excesses in all examples were explained by sterici nteractions between aryl substituento ft he trieneophile 90 and 7-membered ring of the higherene 68 a.P rotonation followed by an oxidation process provided the target products 89.…”
Section: Troponoid Systems In Organocatalytic Higher-order Cycloadditmentioning
confidence: 99%
“…7,8 In 2019, our research group demonstrated the application of 2-benzyl-1,4-naphthoquinones as a novel group of 4πcomponents in the organocatalytic [6 + 4]-cycloaddition with 8,8-dicyanoheptafulvene (Scheme 2). 9 A distinctive feature of the strategy was the transformation of these substrates into the corresponding dienolates under mild, organic Brønsted base catalytic conditions and their application as higherenophiles in the higher-order cycloaddition. Given the promising synthetic potential of such an approach, studies on the development of a new higher-order cycloaddition proceeding under Brønsted base catalysis were undertaken (Scheme 2).…”
Section: ■ Introductionmentioning
confidence: 99%
“…The higher-order cycloadditions involving troponoid systems have received much attention for their capacity to construct important medium-sized polycyclic scaffolds directly. [1] In this context, the cycloaddition chemistry of heptafulvenes has been explored in great detail, in which heptafulvene acts either as a 6π, or 8π component to undergo [6 + 3]-, [2] [6 + 4]-, [3] or [8 + 2]cycloadditions (Scheme 1a). [4] However, to the best of our knowledge, there have been no reports on [8 + 3]-cycloadditions involving heptafulvenes.…”
Section: Introductionmentioning
confidence: 99%